2002
DOI: 10.1029/2001jd001159
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical modeling of the 1999–2000 Arctic winter 2. Chlorine activation and ozone depletion

Abstract: The effect of polar stratospheric clouds (PSCs) on ozone depletion during the 1999–2000 Arctic winter has been assessed using a coupled microphysical/photochemical model. Scenarios spanned a large range of denitrification levels, with up to 80% vortex‐averaged denitrification and localized dehydration. PSC composition was varied, exploring sensitivity to heterogeneous reaction rates. PSC formation during February was critical in causing severe ozone depletion below 500 K. Heterogeneous chemistry on these PSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…4.2.2 of WMO, 2007); indeed Santee et al (2008) have recently shown that the usual equilibrium models of NAT are quite inaccurate, especially in the Arctic, and that microphysical models (likely prohibitive for a CCM) are required. Second, chlorine activates very effectively on liquid aerosols at low temperatures, which in contrast to NAT are well understood, and which likely account for the majority of the aerosol in the Arctic ; moreover the effects of denitrification on ozone loss appear to be relatively small, at most 30% and usually much less (Drdla and Schoeberl, 2002;WMO, 2007).…”
Section: Model Datamentioning
confidence: 99%
“…4.2.2 of WMO, 2007); indeed Santee et al (2008) have recently shown that the usual equilibrium models of NAT are quite inaccurate, especially in the Arctic, and that microphysical models (likely prohibitive for a CCM) are required. Second, chlorine activates very effectively on liquid aerosols at low temperatures, which in contrast to NAT are well understood, and which likely account for the majority of the aerosol in the Arctic ; moreover the effects of denitrification on ozone loss appear to be relatively small, at most 30% and usually much less (Drdla and Schoeberl, 2002;WMO, 2007).…”
Section: Model Datamentioning
confidence: 99%
“…It has been shown that the large particles observed in January to March 2000 Northway et al, 2002) are unlikely to have been nucleated on synoptic-scale ice , as has been assumed in previous models of denitrification (Waibel et al, 1999;Kondo et al, 2000), although the role of mesoscale ice clouds remains uncertain. The simulations have also shown that NAT particles with concentrations as low as those observed can efficiently denitrify the Arctic lower stratosphere (Drdla et al, 2002;Mann et al, 2002Mann et al, , 2003. In previous studies Mann et al, 2002Mann et al, , 2003 we have highlighted the importance of the dynamical state of the vortex for efficient denitrification by sedimentation of very low concentrations of particles.…”
Section: Introductionmentioning
confidence: 90%
“…Stratospheric variations in aerosol optical depth can significantly affect heterogeneous chemistry that leads to ozone depletion because particle surface areas are directly proportional to the optical depth. Below we consider how the continuous presence of volcanic cloudy-like conditions in the Arctic can affect springtime ozone loss processes (13)(14)(15)(16)(17)(18) in a cold year such as the winter of 1999-2000.…”
Section: Volcanic Aerosol Effectsmentioning
confidence: 99%
“…We increased sulfate volume mixing ratio (29) in the model from 0.17 ppbv (nonvolcanic) to 20 ppbv (volcanic) to account for volcanic aerosol effects on ozone. We used the Integrated MicroPhysics and Aerosol Chemistry on Trajectories (IMPACT) model in a quasi-three-dimensional mode (15,16) to obtain the results shown. Nearly 3,000 initial points were distributed evenly (in both horizontal and vertical directions) inside the Arctic vortex on Jan. 15, 2000 between Ϸ450 and 700 K surface.…”
Section: Volcanic Aerosol Effectsmentioning
confidence: 99%
See 1 more Smart Citation